1995
DOI: 10.1029/95gl00880
|View full text |Cite
|
Sign up to set email alerts
|

Production of dicarboxylic acids in the Arctic atmosphere at polar sunrise

Abstract: An homologous series of low molecular weight dicarboxylic acids (C2–C11) have been measured in the arctic aerosol samples collected from July 1987 to June 1988 in Alert. Oxalic acid (C2) was found as the dominant species followed by malonic (C3) or succinic (C4 acid. At the time of polar sunrise, certain dicarboxylic acids in arctic haze aerosols became 5 to 20 times more abundant than in the preceding dark winter months. Furthermore, they are correlated with tropospheric ozone depletion events marked by parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…This new reaction pathway involves reactions of Criegee intermediates in the condensed phase with aldehydes, ketones and alkenes and it does not involve acidity. Kawamura et al (1995Kawamura et al ( , 1996Kawamura et al ( , 2005 and Narukawa et al (2003) provide experimental evidence that Br chemistry in the Arctic transforms unsaturated diacids to smaller saturated acids. Ozonolysis of oleic and linoleic acid is shown to contribute to activation of particles to cloud droplets (Broekhuizen et al, 2005).…”
Section: Chemical Ageing Of Aerosolsmentioning
confidence: 99%
“…This new reaction pathway involves reactions of Criegee intermediates in the condensed phase with aldehydes, ketones and alkenes and it does not involve acidity. Kawamura et al (1995Kawamura et al ( , 1996Kawamura et al ( , 2005 and Narukawa et al (2003) provide experimental evidence that Br chemistry in the Arctic transforms unsaturated diacids to smaller saturated acids. Ozonolysis of oleic and linoleic acid is shown to contribute to activation of particles to cloud droplets (Broekhuizen et al, 2005).…”
Section: Chemical Ageing Of Aerosolsmentioning
confidence: 99%
“…It is hypothesized to account for the anomalous CO and CO 2 levels found in some Greenland ice core records, which exceed those in contemporaneous Antarctic records by up to 130 ppbv and 20 ppmv, respectively (Haan and Raynaud, 1998;Tschumi and Stauffer, 2000). A comparison of the organic content in both polar ice caps shows that the Greenland ice cores are enriched by the organic aerosol released in major boreal forest fires during the last two millennia (Gayley and Ram, 1985;Kawamura et al, 1995;Desideri et al, 1998;Savarino and Legrand, 1998). Hoffmann and coworkers found that the photodegradation of dissolved organic matter trapped in ice cores by ultraviolet Cerenkov radiation from cosmic muons can account for the anomalous CO and CO 2 levels, and the correlation between them (Colussi and Hoffmann, 2003;Guzman et al, 2007;Guzman, 2007).…”
Section: Photophysics and Photochemistrymentioning
confidence: 99%
“…There are gaps in the enrichment time series because of this criterion (Figure 13) Relative humidity is raised from 5% (prevailing humidity during observation) to ambient arctic relative humidity. It is likely that particulate Br and associated soluble organic aerosols [Kawamura et al, 1995] are being formed and depositing on all particles according to the surface area distribution (Figures 1 and 11). The fact that a correlation exists only for 0.6-1.0/•m ESD dry aerosol indicates that this size range is the only one in which substantive changes in the particle number distribution are occurring.…”
Section: Comparison Of Denuder and High-volume Sampler Particulate Mementioning
confidence: 99%